Development and evaluation of a games-based informatics module using digital interactive boards - Ettin Maira; Faisal Ashar; Titi Sri Wahyuni; M. Giatman (Journal of Educational and Learning Studies, 2026)
This study aimed to develop an Informatics learning module based on Games-Based Learning (GBL) integrated with a Digital Interactive Board (PID) and to evaluate its validity, practicality, and effectiveness in improving students' learning outcomes. This research employed a Research and Development (R&D) approach using the ADDIE model, comprising Analysis, Design, Development, Implementation, and Evaluation stages. The study involved 33 Grade IX students of SMP Negeri 21 Padang. Data were collected through expert validation questionnaires, teacher and student response questionnaires, and pretest-posttest assessments. The module achieved very high validity scores, including 90.74% for module design, 91.67% for learning materials, and 97.50% for assessment instruments. The practicality scores reached 86.03% for teachers and 80.00% for students. The classical learning mastery rate increased to 90.91%, and the N-Gain score was 0.60, indicating moderate improvement. The GBL module integrated with PID is valid, practical, and effective for improving Informatics learning outcomes at the junior secondary school level